2014
DOI: 10.1089/neu.2010.1512
|View full text |Cite
|
Sign up to set email alerts
|

Functionally-Detected Cognitive Impairment in High School Football Players without Clinically-Diagnosed Concussion

Abstract: Head trauma and concussion in football players have recently received considerable media attention. Postmortem evidence suggests that accrual of damage to the brain may occur with repeated blows to the head, even when the individual blows fail to produce clinical symptoms. There is an urgent need for improved detection and characterization of head trauma to reduce future injury risk and promote development of new therapies. In this study we examined neurological performance and health in the presence of head c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
486
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(535 citation statements)
references
References 39 publications
(49 reference statements)
24
486
1
1
Order By: Relevance
“…2,11,44,61,100 The issue relating to the effects of subconcussive impacts is controversial as researchers and clinicians are divided on the true effects. 4,40,44,67,74,103 Some research 74 has reported that these impacts have minimal effect on cognitive functions, while others 4,40,67,89,103 have reported these to be detrimental to cerebral and cognitive functions. To date, there is a paucity of evidence to identify the impact acceleration that is adequate to produce a non-structural brain injury associated with the neuronal changes of concussion.…”
Section: Impact Thresholdmentioning
confidence: 99%
See 2 more Smart Citations
“…2,11,44,61,100 The issue relating to the effects of subconcussive impacts is controversial as researchers and clinicians are divided on the true effects. 4,40,44,67,74,103 Some research 74 has reported that these impacts have minimal effect on cognitive functions, while others 4,40,67,89,103 have reported these to be detrimental to cerebral and cognitive functions. To date, there is a paucity of evidence to identify the impact acceleration that is adequate to produce a non-structural brain injury associated with the neuronal changes of concussion.…”
Section: Impact Thresholdmentioning
confidence: 99%
“…It has been suggested 100, 103 that brain injuries not only come from concussive events but also from the accrual of subconcussive impacts that can result in pathophysiological changes in the brain. There are numerous studies 2,4,35,40,67,89,103 published that have demonstrated that the accumulation of subconcussive blows can result in neurophysiological changes. However, similar to the literature focused on concussion and mild traumatic brain injury (mTBI), the literature on subconcussive head trauma is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pediatric series of 21 male high school football players with no prior history of concussion, 134 fMRI revealed alterations in the pattern and amplitude of BOLD signal differences when performing the 2-back and 1-back memory tasks, particularly in the middle and superior temporal gyri in 4 athletes who sustained a concussion during the football season. Interestingly, in 4 other players who did not sustain a concussion, fMRI revealed significantly decreased activation levels in the dorsolateral prefrontal cortex and cerebellum, regions of the brain which are associated with working memory.…”
mentioning
confidence: 97%
“…In a study of high school football players, the number of helmet impacts >20 g recorded in a single season ranged from a low of 226 (average, 4.7 per session) to a high of 1855 (average, 38.6 per session). 1 Most of these impacts do not result in the clinical diagnosis of a concussion; however, it is not known if the cumulative effects of these impacts can result in increased damage to the brain. mTBI has been extensively modeled in mice and rats.…”
mentioning
confidence: 99%